Álvarez de Arenales and the system of divisions during the independence of the Audiencia of Charcas - Mamani Siñani, Roger L. (2021)
This work analyzes the armed struggle in the territory of the Audiencia de Charcas during the war of Independence with the system of divisions, an organization carried out by Juan Antonio Álvarez de Arenales, who ordered and coordinated the actions of different guerrilla groups under the umbrella conferred by the titles granted by the authorities of the United Provinces of Río de la Plata. It describes the structure that was implemented, the operation, the leaders and the troops that were part of that organization.